Single Objective Supply Chain Network Optimization around Acrylonitrile Plant - Özçelik, Zehra; Armay, Sinem; Özçelik, Yavuz (International Journal of Contemporary Economics and Administrative Sciences, 2019)
In this study, a profit oriented supply chain network optimization is performed on an acrylonitrile plant. The network consists of three suppliers which provide two necessary raw materials (propylene and ammonia) for the production of acrylonitrile, one production plant and four customers. In the transportation of the raw materials and product, either highway transportation or sea transportation can be preferred with respect to constraints to achieve maximum profit. To investigate the effects of alternative transportation modes of raw materials and product, constraints for raw materials purchased from suppliers, product sold to customers and production capacity of the plant on profit maximization, four cases are performed within the framework of this study. In the solution of this single objective optimization problem GAMS, MATLAB and Solver Tool of Excel are used. In MATLAB, “fmincon” solver; in GAMS program “Cplex”, “LindoGlobal” and “Baron” solvers are preferred whereas “Simplex” is used in Excel. According to the results obtained in each program, it is seen that maximum achievable profit changes from 3,869,389 to 4,664,841 /year and amount of acrylonitrile produced is 79,040 tonnes/year (in the first two cases) and 90,000 tonnes/year (in the consecutive two cases).